The Impact of Childhood Attention-Deficit/Hyperactivity Disorder (ADHD) on Children's Health-Related Quality of Life: A Systematic Review and Meta-Analysis. Issue 6 (April 2023) - Wanni Arachchige Dona, Sithara; Badloe, Nalini; Sciberras, Emma; Gold, Lisa; Coghill, David; Le, Ha N. D.
Objective: To investigate the association between children's health-related quality of life (HRQoL) and childhood attention-deficit/hyperactivity disorder (ADHD). Method: Databases were systematically searched for peer-reviewed literature published between 2010 and 2022. Two reviewers independently screened and assessed the quality of included studies. Meta-analysis was conducted for studies that used the Pediatric Quality of Life Inventory (PedsQL). Results: Twenty-three studies were included, with most rated as "good" quality. Meta-analysis found "very large" effect in both parent- (Hedges' g −1.67, 95% CI [−2.57, −0.78]) and child-reported (Hedges' g −1.28, 95% CI [−2.01, −0.56]) HRQoL for children with ADHD compared to children without ADHD. No difference between parent- and child-reported HRQoL in children with and without ADHD was found. However, parent-reported HRQoL was lower than child-reported HRQoL among children with ADHD. Conclusion: ADHD was associated with substantially poorer children's HRQoL. Among children with ADHD, parents rated their children's HRQoL lower than the children themselves.